Preparation and Characterization of Cu2ZnSnS4 Thin Films and Solar Cells Fabricated from Quaternary Cu-Zn-Sn-S Target - Min Xie; Daming Zhuang; Ming Zhao; Zuolong Zhuang; Liangqi Ouyang; Xiaolong Li; Jun Song (International Journal of Photoenergy)
CZTS thin films were fabricated through sputtering from a quaternary Cu-Zn-Sn-S target, followed by a sulfurization process. CZTS thin-film solar cells were also fabricated and a highest efficiency of 4.04% was achieved. It has been found that obvious Zn loss occurs during the sputtering and poorly crystallized CZTS are formed in the sputtered films. The Zn loss leads to the appearance of SnS. A sulfurization process can obviously improve the crystallinity of CZTS and films with grain size of several hundred nanometers can be obtained after sulfurization. The optical band gap of the films is estimated to be 1.57 eV. The electrical properties of the 4.04% efficient solar cell were investigated and it has been found that cell has obvious deficiency in minority carrier lifetime. This deficiency should be responsible for the low Jsc and low Voc of our cell.